Multinomial Choice with Social Interactions: Occupations in Victorian London - Guerra, José-Alberto; Mohnen, Myra (The Review of Economics and Statistics, 2022)
We study the importance of social interactions on occupational choice in Victorian London using a multinomial choice model within an incomplete social network. Individuals form heterogeneous rational expectations about their peers' behaviors, taking into account their characteristics and the strength of their ties. We show the conditions under which the endogenous, exogenous, and correlated effects can be identified and a unique equilibrium can be established, Using a novel data set, we proxy social groups by parish boundaries and strength of ties by geographic distances, Our results show the importance of the endogenous effects and reveal distinct effects by occupation.